Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1161/01.hyp.0000088561.17252.42
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Carbon Monoxide and Adenosine in the Nucleus Tractus Solitarii of Rats

Abstract: Abstract-Carbon monoxide has been identified as an endogenous biological messenger in the brain. Heme oxygenase catalyzes the metabolism of heme to carbon monoxide and biliverdin. Previously, we have shown the involvement of carbon monoxide in central cardiovascular regulation, baroreflex modulation, and glutamatergic neurotransmission in the nucleus tractus solitarii of rats. We also showed that adenosine increased the release of glutamate in the nucleus tractus solitarii. In this study, we investigated the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
2
13
1
Order By: Relevance
“…1, A and B). These results were similar to our previous findings (Lo et al, 2000;Lin et al, 2003). It has been shown that administration of an HO inducer such as heme-L-arginate or heme-L-lysinate causes a marked decrease in BP in spontaneously hypertensive rats (Johnson et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…1, A and B). These results were similar to our previous findings (Lo et al, 2000;Lin et al, 2003). It has been shown that administration of an HO inducer such as heme-L-arginate or heme-L-lysinate causes a marked decrease in BP in spontaneously hypertensive rats (Johnson et al, 1996).…”
Section: Discussionsupporting
confidence: 92%
“…In agreement with our previous finding, intra-NTS microinjection of hemin (1 nmol), a heme molecule cleaved by HO to yield CO, resulted in hypotension and bradycardia (Lo et al, 2000;Lin et al, 2003). The administration of vehicle (30% 0.1 N NaOH) itself elicited only slight cardiovascular effects, and the pattern of response was different from that of hemin.…”
Section: Cardiovascular Effects Of Hemin In the Ntssupporting
confidence: 91%
See 1 more Smart Citation
“…It has recently been pointed out that carbon monoxide formed within the nucleus tractus solitarii subserves a vasodepressor mechanism that is tonically active in awake rats (Johnson et al, 1997). We have previously reported that unilateral microinjection of hemin or hematin, a heme molecule cleaved by heme oxygenase to yield carbon monoxide, into the nucleus tractus solitarii of anesthetized rat produces dose-related depressor and bradycardic effects (Lo et al, 2002;Lin et al, 2003). On the other hand, prior administration of the heme oxygenase inhibitor zinc protoporphyrin IX or zinc deuteroporphyrin 2,4-bis gly-col (ZnDPBG) attenuated the depressor and bradycardic effects of hemin (Lin et al, 2003).…”
mentioning
confidence: 99%
“…These results were consistent with our previous findings. 7,8 Pretreatment with PD98059 did not elicit significant cardiovascular responses ( Figure 1A). Interestingly, the depressor and bradycardic responses of the same dose of adenosine in the NTS were attenuated 10 minutes after PD98059 treatment (Ϫ37.9Ϯ2.9 versus Ϫ21.7Ϯ3.1 mm Hg and Ϫ78.6Ϯ13.2 versus Ϫ52.9Ϯ12.0 bpm, respectively; PϽ0.05, paired t test; nϭ6; Figure 1A and 1B).…”
Section: Effects Of Mek Inhibitor On Cardiovascular Responses To Adenmentioning
confidence: 97%